2016
DOI: 10.3390/molecules21111549
|View full text |Cite|
|
Sign up to set email alerts
|

Podophyllotoxin-Loaded Nanostructured Lipid Carriers for Skin Targeting: In Vitro and In Vivo Studies

Abstract: Nanostructured lipid carriers (NLC) exhibit high skin targeting efficiency and good safety. They are promising vehicles for topical drug delivery. This study aims to increase the skin distribution of podophyllotoxin (POD) by incorporating it into NLCs. Two kinds of POD-loaded NLCs (POD-NLCs)-POD-NLC formulation 1 and POD-NLC formulation 2 -were prepared and characterized. Their skin targeting efficiencies were compared by conducting in vitro and in vivo experiments. Obviously smaller mean particle size was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…Nanoparticles with mucoadhesive properties have previously been used to facilitate drug administration to the mucosa and improve the active effects of transmucosal administration ( 31 ). In the present study, in vitro experimentation indicated that the residence time of POD-NLCs was increased compared with POD-T. POD-NLCs enable sustained drug delivery for 60 h, consistent with results of a previous study, which used POD-NLCs for targeted drug delivery ( 12 ). In the present study, the in vivo drug release from POD-NLCs in Tibetan miniature pigs was monitored by detecting the amount of POD in the cervical mucus and mucosal tissue.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Nanoparticles with mucoadhesive properties have previously been used to facilitate drug administration to the mucosa and improve the active effects of transmucosal administration ( 31 ). In the present study, in vitro experimentation indicated that the residence time of POD-NLCs was increased compared with POD-T. POD-NLCs enable sustained drug delivery for 60 h, consistent with results of a previous study, which used POD-NLCs for targeted drug delivery ( 12 ). In the present study, the in vivo drug release from POD-NLCs in Tibetan miniature pigs was monitored by detecting the amount of POD in the cervical mucus and mucosal tissue.…”
Section: Discussionsupporting
confidence: 92%
“…A previous study reported that NDCs improve the physical and chemical properties of drugs, provide sustained, targeted release and reduce systemic absorption ( 10 ). Nanostructured lipid carriers (NLCs) are a novel type of NDC developed from solid lipid nanoparticles, in which a solid matrix is blended with a fluid lipid to improve drug loading capacity and release properties ( 10 12 ). NLCs are able to adhere to the skin surface and transport drugs in a controlled manner, while causing minimal irritation ( 13 ).…”
Section: Introductionmentioning
confidence: 99%
“…The motion of the hair may likewise add to the penetration of nanoparticles of a size of 20 nm. 97 Lipids that resemble the composition of sebum may likewise advance follicular penetration as a high sebum/water partition coefficient is a basic characteristic for transport into HF. Epidermal targeting may also be assumed due to a dissolution or erosion of…”
Section: Skin Targetingmentioning
confidence: 99%
“…Nanostructured lipid carriers (NLC), a novel type of delivery system, exhibit high skin targeting efficiency and good safety (Zhao et al, 2016). Compared with traditional POD tincture, POD-NLC was able to adhere to the skin surface and transport POD in a mild and controlled manner, minimizing irritation and toxicity (Zhao et al, 2016;Gao et al, 2018). To date, there is no evidence showing any therapy is superior to another, nor is any strategy suitable for all patients with genital warts.…”
Section: Dear Editormentioning
confidence: 99%